Psycho-educational practices and the problem of educability: school as emergency area - Baquero, Ricardo (2005)
The present article tries, in the first term, to analyze certain present problems in the definition, uses and supposition that he(she) adopts the notion of «educabilidad» and of «conditions of educabilidad «of the subjects. Especially the presence of suppositions will be analyzed psicoeducativos in the conceptions on educabilidad and his relation with the reasons attributed to the school massive failure. In the second term, there will be tried to show the fertility of a work of investigation on two questions that escenifican the presence of the suppositions analyzed concerning the educabilidad and the school failure: the analysis of the procedures and criteria psicoeducativos used for the diagnosis and forecast of the possibilities of learning of the pupils and the analysis of educational experiences or psicoeducativas alternative of attention to the school massive failure.